Impact of weighted average cost of capital, capital expenditure, and other parameters on future utility‐scale PV levelised cost of electricity. (29th August 2019) - Vartiainen, Eero; Masson, Gaëtan; Breyer, Christian; Moser, David; Román Medina, Eduardo
Abstract: Solar photovoltaics (PV) is already the cheapest form of electricity generation in many countries and market segments. Market prices of PV modules and systems have developed so fast that it is difficult to find reliable up to date public data on real PV capital (CAPEX) and operational expenditures (OPEX) on which to base the levelised cost of electricity (LCOE) calculations. This paper projects the future utility‐scale PV LCOE until 2050 in several European countries. It uses the most recent and best available public input data for the PV LCOE calculations and future projections. Utility‐scale PV LCOE in 2019 in Europe with 7% nominal weighted average cost of capital (WACC) ranges from 24 €/MWh in Malaga to 42 €/MWh in Helsinki. This is remarkable since the average electricity day‐ahead market price in Finland was 47 €/MWh and in Spain 57 €/MWh in 2018. This means that PV is already cheaper than average spot market electricity all over Europe. By 2030, PV LCOE will range from 14 €/MWh in Malaga to 24 €/MWh in Helsinki with 7% nominal WACC. This range will be 9 to 15 €/MWh by 2050, making PV clearly the cheapest form of electricity generation everywhere. Sensitivity analysis shows that apart from location, WACC is the most important input parameter in the calculation of PV LCOE. Increasing nominal WACC from 2 to 10% will double the LCOE. Changes in PV CAPEX and OPEX, learning rates, or market volume growth scenarios have a relatively smaller impact on future PV LCOE. Abstract : Utility‐scale PV LCOE in Europe with 7% nominal WACC ranges from 24 €/MWh in Malaga to 42 €/MWh in Helsinki in 2019 and will be 9‐15 €/MWh by 2050, making PV clearly the cheapest form of electricity generation. With location, WACC is the most important LCOE input parameter: increasing nominal WACC from 2 to 10% doubles the LCOE. Changes in PV CAPEX and OPEX, learning rates, or market volume growth have a relatively smaller impact on future LCOE.